Sleep and quality of life in college students:comparison between sexes - Reis, Anaïs (2022)
College students are undergoing major academic and psychosocial pressures and show preference for evening activities. Due to the increasing enrollment in higher education and the propensity for sleep problems could jeopardize the health, academic performance and quality of life, the goal was to analyze the relationship between perceptions of quality of sleep (QS) and the perception of quality of life (QoL) among college students, comparing sexes.